2022
DOI: 10.1136/bmj-2022-071416
|View full text |Cite
|
Sign up to set email alerts
|

Risk of preterm birth, small for gestational age at birth, and stillbirth after covid-19 vaccination during pregnancy: population based retrospective cohort study

Abstract: Objective To assess the risk of preterm birth, small for gestational age at birth, and stillbirth after covid-19 vaccination during pregnancy. Design Population based retrospective cohort study. Setting Ontario, Canada, 1 May to 31 December 2021. Participants All liveborn and stillborn infants from pregnancies conceived at least 42 weeks before the end of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 31 publications
0
43
1
2
Order By: Relevance
“…There have now been several large population studies that examine the impact of COVID-19 vaccination on birth outcomes. [19] , [20] , [45] , [65] , [66] , [67] , [107] , [108] , [109] , [110] , [111] Lower rates of very preterm birth (<32 weeks gestation) was observed in vaccinated pregnant people in Ontario, Canada (34% reduction) and Sweden (22% reduction), [67] but no difference was observed in Norway. [67] Several studies reported no association of vaccination status with preterm birth, stillbirth, small for gestational age, very low birth weight, infant mortality, or neonatal hospitalizations.…”
Section: Covid-19 Vaccination and Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…There have now been several large population studies that examine the impact of COVID-19 vaccination on birth outcomes. [19] , [20] , [45] , [65] , [66] , [67] , [107] , [108] , [109] , [110] , [111] Lower rates of very preterm birth (<32 weeks gestation) was observed in vaccinated pregnant people in Ontario, Canada (34% reduction) and Sweden (22% reduction), [67] but no difference was observed in Norway. [67] Several studies reported no association of vaccination status with preterm birth, stillbirth, small for gestational age, very low birth weight, infant mortality, or neonatal hospitalizations.…”
Section: Covid-19 Vaccination and Pregnancymentioning
confidence: 99%
“… [67] Several studies reported no association of vaccination status with preterm birth, stillbirth, small for gestational age, very low birth weight, infant mortality, or neonatal hospitalizations. [19] , [20] , [45] , [65] , [66] , [67] , [106] , [107] , [108] , [110] , [111] Two studies reported 40-43% reductions in the rate of stillbirth in vaccinated people and the effect remained even after adjusting for common cofactors. [20] , [110] Another reported a slight decrease in risk for NICU admission in babies born to people receiving at least one-dose compared to those born to unvaccinated people.…”
Section: Covid-19 Vaccination and Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…[41] Other studies have shown a lower risk of stillbirth in those vaccinated, and no evidence for adverse pregnancy outcomes following COVID-19 vaccination. [12, 42] Vaccination coverage among women giving birth has been increasing over time, but uptake remains lower at the time of delivery in women from ethnic minority groups, with lowest vaccination rates in black women, and those living in deprived areas. [11] Interventions to address these inequalities and engagement with pregnant women to ensure uptake of future booster vaccines are needed, since many women who become pregnant may have received their last dose of a vaccine several months previously.…”
Section: Discussionmentioning
confidence: 99%
“…Abortion, of course, isn’t the only medical issue where the voice of the evidence is lost amid populist clamour and political opportunism. This week’s examples are the “zombie policy” of user charges for missed appointments 9 and introducing prostate cancer screening under the guise of “case finding.”10 Isolating the evidence signals from the noise–whether it is about the safety of covid vaccines in pregnancy,11 the new clinical features of monkeypox,1213 or how best to limit sitting time in office based work 14–is as much a responsibility of policy and law makers as it is of clinicians.…”
mentioning
confidence: 99%